Systematic review of the relationships between physical activity and health indicators in the early years (0-4 years) - Valerie Carson; Eun-Young Lee; Lyndel Hewitt; Cally Jennings; Stephen Hunter; Nicholas Kuzik; Jodie A. Stearns; Stephanie Powley Unrau; Veronica J. Poitras; Casey Gray; Kristi B. Adamo; Ian Janssen; et al. (BMC, 2017)
Abstract Background Given the rapid development during the early years (0-4 years), an understanding of the health implications of physical activity is needed. The purpose of this systematic review was to examine the relationships between objectively and subjectively measured physical activity and health indicators in the early years. Methods Electronic databases were originally searched in April, 2016. Included studies needed to be peer-reviewed, written in English or French, and meet a priori study criteria. The population was apparently healthy children aged 1 month to 59.99 months/4.99 years. The intervention/exposure was objectively and subjectively measured physical activity. The comparator was various volumes, durations, frequencies, patterns, types, and intensities of physical activity. The outcomes were health indicators ranked as critical (adiposity, motor development, psychosocial health, cognitive development, fitness) and important (bone and skeletal health, cardiometabolic health, and risks/harm). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework was used to assess the quality of evidence for each health indicator by each study design. Results Ninety-six studies representing 71,291 unique participants from 36 countries were included. Physical activity interventions were consistently (>60% of studies) associated with improved motor and cognitive development, and psychosocial and cardiometabolic health. Across observational studies, physical activity was consistently associated with favourable motor development, fitness, and bone and skeletal health. For intensity, light- and moderate-intensity physical activity were not consistently associated with any health indicators, whereas moderate- to vigorous-intensity, vigorous-intensity, and total physical activity were consistently favourably associated with multiple health indicators. Across study designs, consistent favourable associations with health indicators were observed for a variety of types of physical activity, including active play, aerobic, dance, prone position (infants; ≤1 year), and structured/organized. Apart from ≥30 min/day of the prone position for infants, the most favourable frequency and duration of physical activity was unclear. However, more physical activity appeared better for health. Evidence ranged from "very low" to "high" quality. Conclusions Specific types of physical activity, total physical activity, and physical activity of at least moderate- to vigorous-intensity were consistently favourably associated with multiple health indicators. The majority of evidence was in preschool-aged children (3-4 years). Findings will inform evidence-based guidelines.